(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper investigates the nature of education as a process of influencing pro-environmental behavior (PEB) in young people. A quantitative design was used to gather information on 300 students in form of a survey to analyze the impacts of environmental education (EE), environmental attitudes (EA), and barriers. Hierarchical regression analysis demonstrated here the significant association of EE with PEB, and the addition of EA to this relationship enhanced the relationship, indicating an indirect association between knowledge and behavior with attitudes playing a middle ground in this association. Negative predictors were also a very important barrier, which meant that structural and contextual constraints are an impediment to sustainable practices. Independent-samples t-test showed that female students expressed the PEB more than males, and this fact is in agreement with the previous studies of gender and environmental concern. There were also minor demographic impacts in which older and urban students exhibited a little more engagement in sustainability behaviors. These findings lend credence to the Theory of Planned Behavior by Ajzen (1991) and the Value-Belief-Norm theory by Stern (2000) to the effect that education, attitude, and structural support jointly contribute to pro-environmental action. The research notes that in terms of sustainability among the future generations, education should have the holistic, gender-sensitive, and context-specific approach.